Intellectual property rights and agro-based natural product: Malaysian legal perspective - Mohd Noor, Nor Azlina; Abd Aziz, Ahmad Shamsul (Canadian Center of Science and Education, 2011)
Malaysia is a country which has been blessed with plethora of natural resources and product such as plants and animals. It is an established fact that the agriculture sector part of our natural product contributed substantially to the growth and development of the Malaysian economy. At the same time, it falls as part of the property which must be protected to ensure its sustainability. This paper will look into the right and protection of agro-based natural product specifically to the plant varieties and geographical indications from Intellectual Property Rights perspective in Malaysia.